Learning Community Management in Strengthening Differentiated Learning for Teachers of Tambakrejo 01 Public Elementary School, Gayamsari Sub-District, Semarang - Ida Karima; Endang Wuryandini; Muhammad Prayito (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Teachers play a central role in implementing the Merdeka Curriculum, particularly in differentiated instruction that aligns with students' needs, interests, and readiness. This study aims to describe the management of professional learning communities in strengthening differentiated learning at SD Negeri Tambakrejo 01, Gayamsari District, Semarang City. The research employed a descriptive qualitative approach. Data were collected through in-depth interviews, participatory observation, and document analysis. Data were analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The results indicate that learning community management includes need-based planning, structured role organization, routine implementation through CP-ATP discussions and micro teaching, and supervision by the principal through monitoring and feedback. The "Kombel Bersahabat" serves as an effective collaborative space that supports teachers in enhancing their ability to design and implement differentiated instruction. The study concludes that effective management of learning communities strengthens teacher competence in realizing student-centered learning.